"Karkonoski System Wodociągów i Kanalizacji etap I" - projekt czynu, nie haseł, czyli : jak właściwie promować inwestycje przyszłości - Markowska, Katarzyna ("The Karkonosze Water Supply and Sewage System", First Phase : Promoting Investments of the Future, 2008)
The article is an attempt to present benefits of globalization and possibilities opened up for Poland by suitable spending of union resource. A good example of a project co-financed from the EU Cohesion Fund is „The Karkonosze Water Supply and Sewage System". The aim of this project is to improve the status of natural environment. Its implementation will give the communities of the Karkonosze Mountains varied benefits that are immeasurable. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 402-410